Recovery: Non-work experiences that promote positive states - Sonnentag, Sabine; Niessen, Cornelia; Neff, Angela (The Oxford Handbook of Positive Organizational Scholarship, 2012)
This chapter gives an overview of research on work-related recovery processes. Recovery can be conceptualized as a process that reverses the strain process and that restores well-being. The chapter focuses on the question of how recovery processes improve positive affective states, work engagement, and job performance. The chapter stresses that it may not only be important to gain distance from negative work experiences, but also to capitalize on positive work events and experiences.
Keywords: Job performance; Positive affect; Proactive behavior; Psychological detachment; Recovery; Restoration; Work engagement